2014
DOI: 10.5812/aapm.20326
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamic Parameters of Low-Flow Isoflurane and Low-Flow Sevoflurane Anesthesia During Controlled Ventilation With Laryngeal Mask Airway

Abstract: Background:Nowadays laryngeal mask airway (LMA) is popular as one of the best choices for airway management. Low-flow anesthesia has some advantages like lower pollution, hemodynamic stability and cost effectiveness. Volatile anesthetics are widely used for anesthesia maintenance during operations. Sevoflurane has more hemodynamic stability compared to isoflurane, but there are few studies comparing the hemodynamic stabilities of these two anesthetics during controlled low flow anesthesia with LMA.Objectives:T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…This is associated with good hemodynamic stability and high patient acceptance. [ 10 ] Administration of fentanyl before LMA insertion gives synergistic effect with propofol and sevoflurane. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…This is associated with good hemodynamic stability and high patient acceptance. [ 10 ] Administration of fentanyl before LMA insertion gives synergistic effect with propofol and sevoflurane. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the hemodynamic parameters, Negargar et al [21], in their study DAP, SAP and MAP in the sevoflurane group were significantly lower than the isoflurane group. This might have been due to the effect of sevoflurane on cardiorespiratory reflexes.…”
Section: ! "#$%And!'(!)and*+-#/01!2#3#!+4!3/and!#30and536!#52!27-#30+5!+4!67-and-8! ! 96+4%7-#5and!:-+7!! ;5!<!'=>! ?And@+4%7-#5and!:-+7!mentioning
confidence: 84%
“…The direct vasodilator effect of sevoflurane is considered to be 20% of isoflurane. This weak and vasodilator effect of sevoflurane may help explain why cerebral vasculature remains stable in response to changes in CPP during anaesthesia of sevoflurane, but this is disturbed due to extensive cerebral vasodilatation in isoflurane anaesthesia at the same concentration [21]. In addition, because of this weak vasodilation effect, sevoflurane is likely to cause a marked increase in ICP.…”
Section: ! "#$%And!'(!)and*+-#/01!2#3#!+4!3/and!#30and536!#52!27-#30+5!+4!67-and-8! ! 96+4%7-#5and!:-+7!! ;5!<!'=>! ?And@+4%7-#5and!:-+7!mentioning
confidence: 99%
“…Deepak singh et al ( 2009), [11] concluded that none of the patients demonstrated any haemodynamic instability that required use of rescue drug in Sevoflurane or Isoflurane group. Sohrab negarkar et al (2014), [10] observed that there was increase in SBP in Isoflurane group at 10min, 15min and 30 min than Sevoflurane group which was statistically significant. There was increase in DBP in Isoflurane group at 10 min and 30 min than Sevoflurane group which was statistically significant.…”
Section: Systolic Blood Pressure (Sbp) and Diastolic Blood Pressure (...mentioning
confidence: 88%
“…During Isoflurane anaesthesia, tachycardia may be better controlled with the intermittent use of narcotics which is not used in our study. Sohrab negarkar etal (2014), [10] observed that the mean heart rate was more in Isoflurane group than Sevoflurane group at 25 min(p>0.05). However, the mean heart rate was comparable between the two groups during the study period.…”
Section: Heart Ratementioning
confidence: 93%